Pinning in High-Tc Superconductors - Ernst Helmut Brandt (Active and Passive Electronic Components)
Magnetic flux can penetrate a type-II superconductor in the form of flux-lines or Abrikosov vortices, each of which carry a quantum of flux and arrange in a more or less regular triangular lattice. Under the action of an electric current, these flux lines move and dissipate energy unless they are pinned by material inhomogeneities. In conventional superconductors, depinning occurs when a critical current density Jc is exceeded. In high-Tc superconductors (HTSC), thermally activated depinning causes a finite resistivity t9 even at current densities J ≪ Jc. At sufficiently large temperature T, linear (ohmic) resistivity is observed down to J → 0. This indicates that the flux lines are in a "liquid state" with no shear stiffness and with small depinning energy. At lower T, ρ(J) is highly nonlinear, since the pinning energy increases with decreasing J. In highly anisotropic Bi- and Tl-based HTSC, thermal depinning occurs at rather low T, since short vortex segments ("pancake vortices" in the CuO layers) can depin individually with very small activation energy.